Reactualization of The Role and Function of Islamic Religious Counselors in Minimizing Early Marriage - Irwan Lantasanna; Helmi Kamal; Abbas Langaji; Rudiadi Rudiadi (Institut Agama Islam Negeri Palopo, 2023)
This research aims to determine the strategies by Islamic Religious Counselors in reducing the number of early marriages in the Wara district. The author chooses qualitative research with an empirical approach to Islamic law to analyze social reality in depth. This approach was chosen because the authors wanted to explain an in-depth analysisof Islamic religious extension officers' role in carrying out informative, educative, consultative, and advocative functions in early marriage cases. The subjects in this study were two functional Islamic religious instructors, five non-civil servant Islamic religious instructors, and one BP4 mediator. The object of this study is the role of religious instructors in carrying out professional functions in cases of early marriage. The study results showed that the Islamic Extension Counselors in Wara District performed well because they carried out informative and educative roles and functions, consular and advocative functions as extension agents consistently by conducting direct counselling to the community. The strategies undertaken to reduce the number of early marriages arecounsellingto prevent underage marriages, rejecting underage brides, socializing the importance of formal education to adolescents, and approaching parents to maximize their role in educating children.